2011
DOI: 10.1002/ange.201102901
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Small Gold Clusters with Unique Geometries through Cluster‐to‐Cluster Transformations: Octanuclear Clusters with Edge‐sharing Gold Tetrahedron Motifs

Abstract: Des Pudels Kern: Ein Postsyntheseansatz mit einem Diphosphanliganden lieferte zwei Au8‐Cluster mit einzigartigen Kerngeometrien, die auf kantenverknüpften Gold‐Tetraedern basieren (siehe Bild). Obwohl die Kerne der Cluster isomer sind, unterscheiden sich die Cluster in der Farbe und den optischen Eigenschaften, wofür die Kerngeometrien als Ursache identifiziert wurden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
1
28
0
1
Order By: Relevance
“…Noble metal nanoparticles 1 9 have received significant attention in recent decades due to their unique electronic properties that make them interesting for a wide range of applications, 10 16 in particular, sensing 10 , 12 and catalysis. 13 , 16 If the number of atoms is small, these particles are highly symmetric and exhibit a significant energy gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO).…”
Section: Introductionmentioning
confidence: 99%
“…Noble metal nanoparticles 1 9 have received significant attention in recent decades due to their unique electronic properties that make them interesting for a wide range of applications, 10 16 in particular, sensing 10 , 12 and catalysis. 13 , 16 If the number of atoms is small, these particles are highly symmetric and exhibit a significant energy gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO).…”
Section: Introductionmentioning
confidence: 99%
“…Electrospray ionization mass spectrometry (ESI/MS) has proven to be valuable in monitoring the solution-phase growth [3,4] of coinage metal nanoclusters and to direct their bulk synthesis [3r] as well as to monitor their solution and gas phase reactivity [3,5]. For example, these MS studies have revealed that the growth of bis-phosphine capped gold nanoclusters, upon reduction of Au(I) salts by sodium borohydride, is complex and depends on a range of factors including: (i) the solvent(s), (ii) the type of reductant, (iii) the gold salt, (iv) the steric and geometric constraints of the bis-phosphine and, (v) the molar ratio of the Au(I) salt to the bis-phosphine.…”
Section: Introductionmentioning
confidence: 99%
“…Clusters with 8 gold atoms, in contrast, tend to adopt rather less symmetric structures, such as the 'core + exo' geometries of [Au 8 (dppp) 4 ] 2+ and [Au 8 (dppp) 4 X 2 ] 2+ , X=Cl − , PhC≡C − (Fig. 1) where an octahedral Au 6 core is capped by two 'exo' gold atoms 14,15 , or the highly distorted cube reported recently for [Au 8 (PPh 3 ) 8 ] 2+ 13 .…”
mentioning
confidence: 99%